The Factors That Influence Audit Delay In Manufacturing Companies Listed On The Indonesia Stock Exchange 2016-2017 - Ester Verawati; Yuniatin Trisnawati D.K.W (Common Publisher, 2019)
Financial report is something that is very important for the sustainability of companies,especially companies that have gone public. One measure of accuracy in the submission of relevant financial statements is audit delay. This Research purposed to analyze and measure firm specific factors that influencing the audit delay, by using five independent variables there are : (1) Company Size, (2) Profitability, (3) Solvability, (4) Public Accountant Size, And (5) Auditor’s Opinion. The data was used in this research is the secondary data gotten directly by visiting the Indonesia Stock Exchange, there are the annual report of manufacturer companies 2016-2017. Sample this research is a number of 148 companies selected using purposive sampling method. Data analysis in this research using multiple linear regression analysis. The result of this research showed that profitability has positive influences on audit delay. Company size, solvability, public accountant size, and auditor’s opinion have negative influences on audit delay. The result of this research showed that these five factors simultaneously influence on Audit Delay. Based on the adjusted R2 value of 7,1% indicates that 7,1% Audit Delay variable explained by company size, profitability, solvability, public accountant size, and audit opinion. While the remaining 92,9% is explained by other variables not examinated in this study.